Associations between school-based fluoride mouth-rinse program, medical-dental expense subsidy policy, and children's oral health in Japan: an ecological study - Takafumi Yamamoto; Sakura Kiuchi; Miho Ishimaru; Hideki Fukuda; Tetsuji Yokoyama (BMC Public Health, 2024)
Background Dental caries are a common non-communicable disease among children. As a public health measure at the prefectural level, school-based fluoride mouth-rinse (S-FMR) program, medical/dental expense subsidy policies, and other factors may reduce the incidence of dental caries and tooth loss. Prefectures focusing on promoting oral health policies may promote both, but the interaction effect of implementing both subsidy policies and S-FMR at the prefectural level on caries prevention has not yet been examined. Methods We conducted an ecological study using two-wave panel data, prefecture-level aggregated data in Japan for 2016 and 2018. Coefficient and 95% confidence intervals (CI) were calculated for the dependent variables for oral health using mixed-effects linear regression analysis adjusted for possible confounders. Two dependent variables were used; the standardized claim ratio (SCR) of deciduous tooth extraction and 12-year-olds’ decayed, missing, or filled permanent teeth (DMFT). Four independent variables were S-FMR, the SCR of dental sealants, prefectural income per person, and subsidy policy in three models: co-payment until children enter elementary school (n = 23), no co-payment until children enter elementary school (n = 7), and co-payment continuing beyond elementary school (n = 17). The effects of six interaction terms, each representing a unique pairing from the four independent variables, were individually calculated. Results S-FMR was negatively associated with the SCR of deciduous tooth extractions and DMFT (coefficient = -0.11, 95% CI -0.20; -0.01 and coefficient = -0.003, 95% CI -0.005; -0.001, respectively). No co-payment until children enter elementary school was positively associated with the SCR of deciduous tooth extraction compared to co-payment until children enter elementary school(coefficient = 11.42, 95% CI 3.29; 19.55). SCR of dental sealants was positively associated with the SCR of deciduous tooth extractions (coefficient = 0.12, 95% CI 0.06; 0.19) but negatively associated with DMFT (coefficient = -0.001, 95% CI -0.003; -0.0001). Per capita prefectural income was positively associated with the SCR of deciduous tooth extractions(coefficient = 0.01, 95% CI 0.001; 0.02). No interaction was found between S-FMR and the subsidy policy at both outcomes. Conclusion High S-FMR utilization and no co-payment until children enter elementary school were associated with fewer deciduous tooth extractions. Also, S-FMR and dental sealant were associated with decreased DMFT.